2014
DOI: 10.5539/ep.v3n3p21
|View full text |Cite
|
Sign up to set email alerts
|

<sup>133</sup>Cesium Uptake by 10 Ornamental Plant Species Cultivated Under Hydroponic Conditions

Abstract: We focused on the Cs uptake capacities of ornamental flowers. Ornamentals have the advantage of beautifying contaminated environments, and this may have therapeutic effects for individuals, especially in disaster areas. Furthermore, the use of ornamental plants will reduce the risk of pollutants entering the food chain. We hypothesized a strong correlation between high aboveground biomass and high Cs uptake in plants. We assessed the potential of 10 ornamental plant species for remediation of 133 Cesium in hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…The K content in heather honey was not significantly different from the other studied floral origins but tended to be relatively high, while in the case of Rb, it was exceptionally high. 133 Cs is considered to be efficiently taken up by rapeseed [39], but our study showed no accumulation in honey. Otherwise, it was quantified in heather honey (0.24 ± 0.9 mg/kg) and found in polyfloral honeys rich with heather pollen (P2, P3, P8).…”
Section: Element Concentrations In Honey By Its Floral Originscontrasting
confidence: 67%
“…The K content in heather honey was not significantly different from the other studied floral origins but tended to be relatively high, while in the case of Rb, it was exceptionally high. 133 Cs is considered to be efficiently taken up by rapeseed [39], but our study showed no accumulation in honey. Otherwise, it was quantified in heather honey (0.24 ± 0.9 mg/kg) and found in polyfloral honeys rich with heather pollen (P2, P3, P8).…”
Section: Element Concentrations In Honey By Its Floral Originscontrasting
confidence: 67%